CONSTRUCTION OF ISLAMIC RELIGIOUS EDUCATION IN THE ERA OF THE COVID-19 PANDEMIC - Muammar Khadafie (Universitas Muhammadiyah Surakarta, 2023)
This article describes the construction of Islamic Religious Education (PAI) during the Covid-19 pandemic. Restrictions on community activities to break the Covid-19 chain have fundamentally changed the education system in Indonesia. The implementation of learning that was originally carried out face-to-face is now carried out online or virtually. With this change in learning, PAI must adapt to the change itself, so that the purpose of education is to create students who believe and fear God Almighty who have a noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic citizens. and responsibility can be realized. Using the Study Literature Review research method or library research, this article describes the construction of education in the era of the Covid-19 pandemic. The theories and concepts used are learning methods in the Covid-19 era. During the pandemic, learning models and methods in Indonesia generally use Blended Learning and e-Learning. The use of these two learning models is inseparable from the dynamics of government policies related to handling Covid-19. The results of the research found that the learning model that has the potential to be reconstructed in PAI is the blended learning method or model. The blended learning method is used to describe the problems of e-Learning, namely the problem of teachers and the limitations of the internet network. The Blended Learning model is a combination of offline learning methods (face-to-face, etc.) with online learning methods (e-learning).